The poetical works of Edmund Clarence Stedman - Stedman, Edmund Clarence, 1833-1908 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Poetical Works of Edmund Clarence Stedman" by Edmund Clarence Stedman is a comprehensive collection of poetry written during the late 19th century. This volume includes a variety of works that span a range of themes, reflecting the emotional and artistic explorations of the author. As a distinguished figure in American literature, Stedman offers insights into human experience, nature, love, and social issues, showcasing his mastery in crafting both lyrical and narrative poems. The opening of this collection presents sections summarizing the contents, noting contributions from various poems such as (3z(BBohemia: A Pilgrimage(3y (Band (3z(BThe Diamond Wedding.(3y (BIt features imagery that blends the beauty of nature with themes of love and memory, illustrating the journeys and experiences of characters that reflect larger societal narratives. Specific poems such as (3z(BHow Old Brown Took Harper's Ferry(3y (Boffer historical commentary wrapped in poetic form, while (3z(BPenelope(3y (Bengages with classical themes of fidelity and waiting. Overall, the beginning establishes a foundation for Stedman's ongoing exploration of poetic life intertwined with personal and cultural reflections. (This is an automatically generated summary.)s
Release date is 2023-05-14
Bryan Ness and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: American poetry -- 19th century